2016
DOI: 10.1097/md.0000000000004668
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome in patients receiving permanent pacemaker implantation for atrioventricular block

Abstract: A permanent pacemaker (PPM) with dual chamber pacing (DDD) offers atrioventricular synchronization for patients with atrioventricular block (AVB). Single lead atrial synchronous ventricular pacing mode (VDD) is an alternative, but there are concerns about its efficacy and risk of atrial undersensing. Whether VDD can be a good alternative in patients with AVB remains unknown. The aim of the present study was to compare the long-term risk of mortality of VDD with DDD pacing.A total of 207 patients undergoing PPM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…Regarding baseline characteristics, a higher prevalence of men across the study period was observed, which is in accordance with the majority of studies in DDD PM populations [15][16][17]19] and general PM populations [1,2,5,9,12,13,18] except for Scandinavian populations, in which the prevalence of women receiving first DDD PM was reported to be higher than that of men [20,21]. In the present study, the prevalence of men exhibited a statistically significant decreasing trend from 58% in the first decade to 52% in the third decade, which is opposed to observations of a stable proportion of men in successive eras of PM implantation [1,2].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Regarding baseline characteristics, a higher prevalence of men across the study period was observed, which is in accordance with the majority of studies in DDD PM populations [15][16][17]19] and general PM populations [1,2,5,9,12,13,18] except for Scandinavian populations, in which the prevalence of women receiving first DDD PM was reported to be higher than that of men [20,21]. In the present study, the prevalence of men exhibited a statistically significant decreasing trend from 58% in the first decade to 52% in the third decade, which is opposed to observations of a stable proportion of men in successive eras of PM implantation [1,2].…”
Section: Discussionsupporting
confidence: 89%
“…The 1-year survival rate of the present DDD cohort was 96%. These data appear to accord with 1-year overall survival rates from 90.5% to 96% as provided in reports of DDD populations [4,12,15,16] and rates from 91% to 94% as provided in reports of general PM populations [1,5,13,14]. At 5-year follow-up, cumulative survival rate was 82%.…”
Section: Discussionsupporting
confidence: 83%
“…Both heart failure and history of malignancy are well established poor prognostic indicators for mortality after pacemaker placement 9,14 . Heart failure has been estimated to reduce the patient's post‐pacemaker implantation life expectancy by 3.5 years 15 .…”
Section: Discussionmentioning
confidence: 99%
“…This is the typical scenario for paroxysmal/persistent AVB and CRT, where RAA placement enables reliable atrial sensing. Single lead VDD pacemakers were developed to minimize lead-related complications when atrial stimulation is redundant [17,18].…”
Section: Atrial Pacing: Interatrial and Atrioventricular Couplingmentioning
confidence: 99%